The Impact of Religious Tolerance on Professional Interactions in Nigeria’s Multifaith Work Environments - Wachukwu, Chikodi Josiah; Kii, Pius Barinaadaa (NIU Journal of Social Sciences; Vol 11 No 2 (2025): NIU Journal of Social Sciences, Vol. 11 No. 2, June 2025, 2025)
Religious tolerance plays a critical role in shaping professional interactions in multifaith work environments, particularly within culturally and religiously diverse nations like Nigeria. This paper adopts a historical and descriptive method to examine the evolution of religious coexistence in Nigeria and how it informs present-day interpersonal and intergroup dynamics in professional settings. It discusses the mechanisms through which religious tolerance enhances communication, collaboration, and mutual respect among employees from diverse faith backgrounds. The study concludes by offering evidence-based strategies for promoting religious tolerance to enhance workplace harmony and productivity.